2009
DOI: 10.1098/rspb.2009.0817
|View full text |Cite
|
Sign up to set email alerts
|

Brain organization mirrors caste differences, colony founding and nest architecture in paper wasps (Hymenoptera: Vespidae)

Abstract: The cognitive challenges that social animals face depend on species differences in social organization and may affect mosaic brain evolution. We asked whether the relative size of functionally distinct brain regions corresponds to species differences in social behaviour among paper wasps (Hymenoptera: Vespidae). We measured the volumes of targeted brain regions in eight species of paper wasps. We found species variation in functionally distinct brain regions, which was especially strong in queens. Queens from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 78 publications
1
29
0
Order By: Relevance
“…Arneson & Wcislo 2003;Bhadra & Gadagkar 2008). Recent studies have shown a social component to MB plasticity in two species of obligately social paper wasps (Vespidae) with small colonies, which are the only two species studied to date in which dominance is maintained by individual aggressive interactions rather than by pheromones (O'Donnell et al 2006;Molina & O'Donnell 2007Molina et al 2009). Ehmer et al (2001), in contrast, did not find a difference in MB volume between dominant and subordinate wasps of Polistes dominulus wasps, but they did not measure MB subregions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arneson & Wcislo 2003;Bhadra & Gadagkar 2008). Recent studies have shown a social component to MB plasticity in two species of obligately social paper wasps (Vespidae) with small colonies, which are the only two species studied to date in which dominance is maintained by individual aggressive interactions rather than by pheromones (O'Donnell et al 2006;Molina & O'Donnell 2007Molina et al 2009). Ehmer et al (2001), in contrast, did not find a difference in MB volume between dominant and subordinate wasps of Polistes dominulus wasps, but they did not measure MB subregions.…”
Section: Introductionmentioning
confidence: 99%
“…First, if sociality is more cognitively demanding than solitary living, social females should have higher N : K ratios, or larger absolute MB neuropil volume, than solitary reproductives. Second, being part of a group in itself may not influence brain plasticity so much as the demands of achieving and maintaining high dominance status, as suggested by the studies of small-colony paper wasps (O'Donnell et al 2006;Molina & O'Donnell 2007Molina et al 2009). If so, only social queens should have a larger N : K ratio and/or MB neuropil volume than solitary reproductives, while that of social workers should be comparable to solitary bees.…”
Section: Introductionmentioning
confidence: 99%
“…(Fig. 1) Like other eusocial Hymenoptera, paper wasps show behavior-related individual variation in adult brain structure (23)(24)(25). Paper wasp species also differ in the relative amounts of tissue invested in brain regions that process input from different sensory modalities (26).…”
mentioning
confidence: 99%
“…Workers in some species possess large eyes and high visual acuity, whereas others are subterranean species with eyeless workers wholly reliant on olfaction and mechanosensation. We hypothesized that differences among ant species in visual ability could produce variation in C/AO ratios owing to developmental and functional linkages between visually guided behaviour, eye size and OL volume in association with selection for increased (or decreased) visually guided behaviour, resulting in mosaic evolution [18,33,51,75]. Under this hypothesis, workers could evolve larger (or smaller) eyes and OLs with little or no correlated change in AL or C size, although modifications of the C collar region, which receives visual input from the OLs, might be predicted.…”
Section: (E) Visual Ecology and Brain Organization In Antsmentioning
confidence: 99%
“…Even less attention has been given to the scaling of the major primary sensory input neuropils-the antennal (AL) and optic lobes (OL)-which process olfactory and visual afferent information, respectively, and supply the mushroom body calyces (C) in hymenopterans. Understanding how these aspects of brain composition affect worker behaviour and division of labour has been a prominent goal of social insect research, and significant interspecific variation in brain composition associated with task performance has begun to be identified in ants [21,33,47,50] and wasps [51]. Absolute brain size was recently proposed to constrain the evolution of the organization of the functional module comprising the C, AL and OL in polistine wasps [49]; interspecific comparisons suggested that small-brained wasps have lower ratios of C volume to the combined volume of the AL þ OL (C/AO hereafter) owing to positive allometry between C and brain size and negative allometry between AL þ OL and brain size.…”
Section: Introductionmentioning
confidence: 99%